Endoscopic ultrasound-guided entero-enterostomy for the treatment of afferent loop syndrome: a multicenter experience - Brewer Gutierrez, Olaya I.; Irani, Shayan S.; Ngamruengphong, Saowanee; Aridi, Hanaa D.; Kunda, Rastislav; Siddiqui, Ali; Dollhopf, Markus; Nieto, Jose; Chen, Yen-I; Sahar, Nadav; Bukhari, Majidah A.; Sanaei, Omid; Canto, Marcia I.; Singh, Vikesh K.; Kozarek, Richard; Khashab, Mouen A. (Endoscopy, 2018)
Background Afferent loop syndrome (ALS) is traditionally managed surgically and, more recently, endoscopically. The role of endoscopic ultrasound-guided entero-enterostomy (EUS-EE) has not been well described. The aim of this study was to assess the technical and clinical success and safety of EUS-EE.Methods This was a multicenter, retrospective series at six centers in patients with ALS treated by EUS-EE. Data on patients treated with enteroscopy-assisted luminal stenting (EALS) at a single center were also collected. Results 18 patients (mean age 64.2 years, 72 % post-pancreaticoduodenectomy, 10 female) underwent EUS-EE. The most common symptoms were vomiting (27.8 %) and jaundice (33.3 %). Clinical success included resolution of symptoms in 88.9 % and improvement to allow hospital discharge in 11.1 %. Technical success was achieved in 100 % of cases, with a mean procedure time of 29.7 minutes. The most common procedure was a gastro-jejunostomy (72.2 %). Three adverse events (16.7 %) occurred (two mild, one moderate). When compared with data on EALS, patients treated with EUS-EE needed fewer re-interventions (16.6 % vs. 76.5 %; P < 0.001).Conclusion EUS-EE seems to be safe and effective in the treatment of ALS. Indirect comparison with EALS suggested that EUS-EE is associated with a reduced need for re-intervention.